Design of a microgrid energy management system featuring an economic dispatch module and a SCADA interface for real-time data acquisition - Tan, Gillian Anqi (Nanyang Technological University, 2021)
To keep up with distributed energy resources being introduced in the market, microgrids are used to incorporate each energy resource for more reliable operation. These energy resources, such as solar panels, wind turbines and other renewable energy methods, can be used efficiently to supply loads in the same microgrid. Since the microgrid can connect many components together, energy management systems using SCADA are introduced to conveniently control the connected equipment.